LEVEL OF SATISFACTION WITH SOCIO DEMOGRAPHIC PREFERENCES FOR NEIGHBOURHOOD QUALITY - Rahman, Norainah Abdul; Eeda Ali, Nor; Abdullah, Kamariah (Jurnal Arsitektur dan Perencanaan (JUARA), 2019)
This study is focusing on the evaluating the neighbourhood facilities and services by using the socio demographic variables. There are three important variables used which are genders, religions and housing locations. The main purpose of the study is to examine the neighbourhood facilities and services by using level of satisfaction with different socio demographic background.Â  The self-administered questionnaire survey distributed at three neighbourhood area in Manjung District Perak Malaysia with the sample of 421 respondents. To determine the level of satisfaction of different socio demographic background with neighbourhood facilities and services the t-test and one-way ANOVA test were performed. Generally the result shows that all neighbourhood facilities and services are moderate to less level of satisfaction by different socio demographic background. With the detail t-test analysis the result shows that the male are less level of satisfaction then the female. With One-Way ANOVA test analysis for different religions shows that the highest level of satisfaction is Muslim and the lowest level of satisfaction are other religion. While for different housing location the highest level of satisfaction is Lumut and the lowest level of satisfaction is Sitiawan. Based on the result the local authority the Manjung Municipal Council and related religions agencies must be take into account to upgrade and improve the neighbourhood facilities and services in their area for the purpose of neighbourhood quality. With this study the accurate targeted group of people will be identified by the relevant agencies, bodies or local government will tackle and can solve the problems precisely.